2015
DOI: 10.1016/j.evolhumbehav.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Honest signaling in trust interactions: smiles rated as genuine induce trust and signal higher earning opportunities

Abstract: We test the hypothesis that smiles perceived as honest serve as a signal that has evolved to induce cooperation in situations requiring mutual trust. Potential trustees (84 participants from Toulouse, France) made two video clips averaging around 15 seconds for viewing by potential senders before the latter decided whether to ‘send’ or ‘keep’ a lower stake (4 euros) or higher stake (8 euros). Senders (198 participants from Lyon, France) made trust decisions with respect to the recorded clips. If money was sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 35 publications
4
85
0
4
Order By: Relevance
“…In our experiment, females are more attracted to high over low cooperative males, even without having observed them build. Hence, phenotypic cues advertising male cooperativeness may exist in this species, as previously found in humans (Oda et al 2009; Stirrat and Perrett 2010; Stirrat and Perrett 2012; Tognetti et al 2013; Centorrino et al 2015) and in barn owls (Roulin et al 2012). Such cues of cooperativeness could be based on acoustic, olfactory, or visual traits, since all of them are involved in mice communication (e.g., Hurst and Beynon 2004; Musolf et al 2010) and are available to females in our apparatus.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In our experiment, females are more attracted to high over low cooperative males, even without having observed them build. Hence, phenotypic cues advertising male cooperativeness may exist in this species, as previously found in humans (Oda et al 2009; Stirrat and Perrett 2010; Stirrat and Perrett 2012; Tognetti et al 2013; Centorrino et al 2015) and in barn owls (Roulin et al 2012). Such cues of cooperativeness could be based on acoustic, olfactory, or visual traits, since all of them are involved in mice communication (e.g., Hurst and Beynon 2004; Musolf et al 2010) and are available to females in our apparatus.…”
Section: Discussionsupporting
confidence: 55%
“…In humans, morphological facial traits, such as facial width-to-height ratio, advertise cooperativeness and trustworthiness (Stirrat and Perrett 2010; Stirrat and Perrett 2012; Tognetti et al 2013). A genuine smile also seems to be a trait used to estimate cooperativeness (Oda et al 2009; Centorrino et al 2015). In the barn owl ( Tyto alba ), the propensity to cooperate has recently been linked to melanin-based plumage (Roulin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies specifically addressing the issue of partner choice showed that adults preferentially choose individuals who display genuine smiles as cooperative partners (e.g., Johnston, Miles, & Macrae, 2010;Krumhuber et al, 2007;Shore & Heerey, 2011) and also find faces with genuine smiles more approachable (Miles, 2009). Finally, Centorrino, Djemai, Hopfensitz, Milinski, and Seabright (2015) found that adult participants were more willing to invest in people displaying genuine smiles in an economic trust game.…”
Section: Accepted M Manuscriptmentioning
confidence: 98%
“…Those who display more genuine smiles tend to return more money to partners in the investor game (Centorrino, Djemai, Hopfensitz, Milinski, Seabright, 2015). Individuals categorized as stable cooperators in an ultimatum game tend to smile more, in addition to being generally more expressive (Schug, Matsumoto, Horita, Yamagishi, Bonnet, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding what a smile means is important because smiles influence the inferences people draw about others, and decisions about who to trust and cooperate with (Albright et al, 1997;Johnston, Miles, & McCrae, 2010;Schmidt, Levenstein, & Ambadar, 2012;Centorrino, Djemai, Hopfensitz, Milinski, Seabright, 2015;Reed, Zeglen, & Schimdt, 2012). Smiling individuals tend to be rated as more trustworthy, and individuals smiling more intensely are judged more positively (Johnston, Miles, & McCrae, 2010;Schmidt, Levenstein, & Ambadar, 2012).…”
Section: Introductionmentioning
confidence: 99%